A Rare Case Report of Simultaneous Occurrence of Chronic Subdural Hematoma and Acute Extradural Hematoma in a Patient after Multiple Ventriculoperitoneal Shunt Surgeries - Yadav, Vikrant; Prasad, Ravi Shankar (Asian Journal of Neurosurgery, 2023)
Ventriculoperitoneal (VP) shunt surgeries are common neurosurgical procedure for hydrocephalus. Subdural hematoma (SDH) and extradural hematoma (EDH) are rare but potentially life-threatening complications following VP shunt surgeries. We are describing probably the first case in which a 12-year-old boy presented to the emergency room in altered sensorium and gradual onset quadriparesis following multiple shunt revision procedures done in an outside hospital. Computed tomography head showed chronic right-sided frontotemporoparietal chronic SDH and parietal dominant EDH simultaneously with multiple shunt systems in ventricles. Patient was taken for surgery in emergency and emergent evacuation of hematoma was done. Patient improved in the postoperative period. In this case report we will make an attempt to describe a rare complication of VP shunt surgery and possible mechanisms responsible for it.
Keywords: extradural; hematoma; hydrocephalus; subdural; ventriculoperitoneal shunt